Search for Bs0 --> micro+ micro- and B0 --> micro+ micro- decays with 2 fb-1 of pp collisions. - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Aoki, M; Apollinari, G; et al. (2008)
We have performed a search for B(s)(0) --> micro(+) micro(-) and B(0) --> micro(+) micro(-) decays in pp collisions at square root s = 1.96 TeV using 2 fb(-1) of integrated luminosity collected by the CDF II detector at the Fermilab Tevatron Collider. The observed number of B(s)(0) and B0 candidates is consistent with background expectations. The resulting upper limits on the branching fractions are B(B(s)0) --> micro(+) micro(-)) <5.8 x 10(-8) and B(B(0) --> micro(+) micro(-))<1.8 x 10(-8) at 95% C.L.